2023
DOI: 10.14202/vetworld.2023.329-340
|View full text |Cite
|
Sign up to set email alerts
|

Goloba kusi (Hornstedtia scottiana [F. Muell.] K. Schum.) fruit as a feed additive to improve the histological structures and growth performance of broiler

Abstract: Background and Aim: The broiler farming industry in Indonesia has enormous potential, with chicken meat that can be optimized by providing adequate and high-quality feed. However, the main raw material for the feed still relies on imported products, which makes it necessary to produce alternative materials from native plants. Therefore, this study aimed to investigate the effect of giving Goloba kusi fruit (GF) (Hornstedtia scottiana [F. Muell.] K. Schum.) on the growth of the small intestine, pectoralis major… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…The flavonoid in CL also possesses an antioxidant activity that enlarges the myofiber area and protects against free radicals [79,92]. Other experiments have also yielded similar results in which flavonoids play a role in myofiber and fascicle growth [61,72]. Several studies have also reported that flavonoid inclusion in chicken diets directly improves muscle weight [29,93] and induces protein synthesis to promote muscle growth [94].…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…The flavonoid in CL also possesses an antioxidant activity that enlarges the myofiber area and protects against free radicals [79,92]. Other experiments have also yielded similar results in which flavonoids play a role in myofiber and fascicle growth [61,72]. Several studies have also reported that flavonoid inclusion in chicken diets directly improves muscle weight [29,93] and induces protein synthesis to promote muscle growth [94].…”
Section: Discussionmentioning
confidence: 81%
“…The small intestine is one of the prime organs in the digestive tract that absorbs nutrients [ 60 ]. Nutrient absorption efficiency depends on the small intestine’s structure, such as villi length, crypt depth, and the number of goblet cells that secrete mucin [ 61 ]. To achieve the optimal health of poultry, the small intestine should also be healthy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation